Deciding To Be A Widow or Stay with A Husband: The Experience of Muslim Women Filing for Divorce in the Aceh Sharia Court - Ikhwan, M.; Wahyudi, M. Agus; Efendi, Sumardi; Gumilang, Randi Muhammad; Alfiyanto, Afif; Kumalasari, Reni (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2025)
This article examines the lived experiences of Acehnese women who initiate divorce (khulu’), focusing on the socio-religious, cultural, and legal dimensions that shape their decisions. This study employed a qualitative method with a phenomenological approach. The study captures the voices of women from various socio-economic backgrounds through in-depth interviews, aiming to explore their motivations, internal conflicts, and post-divorce realities. Findings indicate that marital dissatisfaction, domestic violence, infidelity, economic independence, and growing awareness of women’s rights are key drivers for seeking divorce. Despite strong religious and cultural norms that often frame divorce as morally undesirable, these women navigate complex legal pluralism and social stigma with remarkable agency. The study underscores how intersecting factors, such as patriarchal interpretations of syarī‘ah, customary values, and legal constraints, impact women’s decision-making processes. Ultimately, the article contributes to the discourse on gender justice, Islamic family law reform, and women's empowerment in Muslim-majority contexts. Policy implications include the urgency of expanding legal aid services, gender-sensitive judicial practices, and community education to uphold women’s rights and dignity in the realm of Islamic marital law.